Effects of diet on postprandial lipaemia: A suggestion for methodological standardization - Karpe, F (1997)
The dietary management of hyperlipoproteinaemia is one of the primary strategies in preventing coronary heart disease (CHD). The effect of reduced calory intake on fasting blood lipids and apolipoproteins by exchanging fat for carbohydrate and replacing saturated dietary fats with vegetable or marine oils are well-documented. The nutritional implications on postprandial triacylglycerolaemia have recently been reviewed (1) and the specific role of polyunsaturated fatty acids in lowering fasting plasma lipids and apolipoproteins has recently been reviewed by Lichtenstein (2). Considerably less is known about diet as a means of modulating postprandial lipoprotein metabolism, which to some extent depends on the fact that pertinent studies have used a variety of methods to provoke the system, ie the composition and size of test meals. As a further complication there is no consensus as to how quantification of postprandial lipids and apolipoproteins should be carried out (3). The present review deals with the effects of diet on postprandial lipaemia and its relevance for the development of CHD. ©1997, Medikal Press.